Circulating Vascular Endothelial Growth Factor (VEGF) Levels in Advanced Stage Cancer Patients Compared to Normal Controls and Diabetes Mellitus Patients with Critical Ischemia - Yoka H. Kusumanto; Coby Meijer; Wendy Dam; Nanno H. Mulder; Geke A.P. Hospers (AboutScience Srl, 2007)
Anti-angiogenic therapy is emerging as a valuable tool in the treatment of patients with cancer. As VEGF is a central target in anti-angiogenic therapy, its levels in the circulation might be relevant in selecting tumor types or patients likely to respond to this treatment. Additional VEGF has been recognized as a key factor in the pathogenesis of diabetic retinopathy. Recently anti-angiogenic therapy has been advocated in this situation. We measured VEGF levels in whole blood in 42 patients with high grade (n = 26) and low grade (n = 16) end stage cancer, and in 28 healthy controls and 37 patients with diabetes related vascular disease. Only 2/26 patients in the group of high grade cancer had signifi  cantly elevated VEGF levels, 1/16 in the low grade group and 1/28 in the healthy control group. In contrast, in 10/37 diabetic patients the mean VEGF levels were signifi  cantly elevated compared to the other groups. The mean level in these diabetic patients was signifi  cantly elevated compared to the other groups. These data indicate the limitation of the use of circulating VEGF levels as a potential selection criterion for anti-angiogenic therapy in cancer patients and suggest further studies into its application in the management of diabetic complications.